High School CS Teacher Preparation: Key Elements, Structure and Challenges - Hazzan , O. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
The talk focuses on high school computer science (CS) education (use of the term Computer Science Education for Didactics of Informatics). Specifically, it aims at presenting a comprehensive picture of high school CS teacher preparation, addressing the structure of high school CS teaching preparation programs, key elements of such programs, i.e., the Methods of teaching CS course and the practicum, and a practical way of building such programs. These topics are briefly described in what follows and will be elaborated in the talk.